INTERNALISASI NILAI GOTONG ROYONG DALAM PENDIDIKAN KARAKTER : MEMBANGUN SOLIDARITAS SOSIAL DI ERA GLOBALISASI - Wahyunita Agustin, Eka; Hayu Kumalasari, Indriani; Azzahra, Nadia; Fifia Maharani, Anita; Althaafena, Maura; Yani, Muhammad Turhan (Universitas Negeri Surabaya (Unesa), 2026)
Globalization can bring major changes to various aspects of Indonesian society, including the erosion of local cultural values ​​such as mutual cooperation. This study aims to examine the concept of internalizing mutual cooperation values ​​in character education, analyzing the challenges that arise in the era of globalization, and developing strategies to strengthen social solidarity through character education. This study uses a qualitative approach with literature study techniques and descriptive analysis. Data were obtained through journals, books, and also relevant scientific articles. The results of this study indicate that internalizing mutual cooperation values ​​has an important role in strengthening attitudes of togetherness, solidarity, and social concern in society. However, these values ​​are increasingly eroded due to increasing individualism in society, the influence of foreign cultures, and dependence on technology. The results of the study also show that in character education this is very important in building social solidarity amidst increasing individualism and the influence of foreign cultures. To answer these challenges, strategies are needed such as integrating mutual cooperation values ​​into the curriculum, project-based learning, collaborative habits, and role models from teachers and the community have proven to be effective in instilling these values ​​in the younger generation. Through character education based on mutual cooperation, it needs to be implemented systematically so that future generations are able to maintain national cultural identity and remain adaptive to the ever-growing global challenges.